Effects of sublethal concentrations of insecticides on the functional response of two mirid generalist predators - Martinou, Angeliki F.; Stavrinides, Menelaos (My University, 2015)
This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.The use of agrochemicals particularly pesticides, can hamper the effectiveness of natural enemies, causing disruption in the ecosystem service of biological control. In the current study, the effects of the insecticides thiacloprid and chlorantraniliprole on the functional response curves were assessed for two mirid predator nymphs, Macrolophus pygmaeus Rambur and Nesidiocoris tenuis Reuter. In the absence of insecticides, both predators exhibited a type II functional response when feeding on eggs of the moth Ephestia kuehniella. N. tenuis seems to be a more efficient predator than M. pygmaeus, as model estimated handling time was significantly lower for the former than for the latter. Residual exposure of M. pygmaeus to sublethal concentrations of either insecticide was associated with a change in the asymptote but not the type of the functional response curve. Thiacloprid seems to be the least compatible with M. pygmaeus, as it led to both a significant reduction of the attack rate and an increase in handling time. In contrast, chlorantraniliprole exposure significantly increased the handling time, but not the attack rate of the predator. Residual exposure of N. tenuis to sublethal concentrations of either insecticide did not have a significant effect on the type nor the parameters of the functional response model. The results show that pesticide residues that do not have lethal effects on beneficial arthropods can reduce prey consumption depending on predator species and on likely risks associated with toxicity.
Keywords: Macrolophus pygmaeus; Nesidiocoris tenuis; Thiacloprid